Production of Solid Fuel by Torrefaction Using Coconut Leaves As Renewable Biomass - Lola Domnina Bote Pestaño; Wilfredo I. Jose (International Journal of Renewable Energy Development, 2016)
The reserves of non-renewable energy sources such as coal, crude oil and natural gas are not limitless, they gradually get exhausted and their price continually increases. In the last four decades, researchers have been focusing on alternate fuel resources to meet the ever increasing energy demand and to avoid dependence on crude oil. Amongst different sources of renewable energy, biomass residues hold special promise due to their inherent capability to store solar energy and amenability to subsequent conversion to convenient solid, liquid and gaseous fuels. At present, among the coconut farm wastes such as husks, shell, coir dust and coconut leaves, the latter is considered the most grossly under-utilized by in situ burning in the coconut farm as means of disposal. In order to utilize dried coconut leaves and to improve its biomass properties, this research attempts to produce solid fuel by torrefaction using dried coconut leaves for use as alternative source of energy. Torrefaction is a thermal method for the conversion of biomass operating in the low temperature range of 200oC-300oC under atmospheric conditions in absence of oxygen. Dried coconut leaves were torrefied at different feedstock conditions. The key torrefaction products were collected and analyzed. Physical and combustion characteristics of both torrefied and untorrefied biomass were investigated. Torrefaction of dried coconut leaves significantly improved the heating value compared to that of the untreated biomass.  Proximate compositions of the torrefied biomass also improved and were comparable to coal. The distribution of the products of torrefaction depends highly on the process conditions such as torrefaction temperature and residence time. Physical and combustion characteristics of torrefied biomass were superior making it more suitable for fuel applications.Article History: Received June 24th 2016; Received in revised form August 16th 2016; Accepted 27th 2016; Available onlineHow to Cite This Article: Pestaño, L.D.B. and Jose, W.I. (2016) Production of Solid Fuel by Torrefaction Using Coconut Leaves As Renewable Biomass. Int. Journal of Renewable Energy Development, 5(3), 187-197.http://dx.doi.org/10.14710/ijred.5.3.187-197